Electrochemical humidity sensor enabled self-powered wireless humidity detection system - Zhang, Mingxiang; Duan, Zaihua; Zhang, Boyu; Yuan, Zhen; Zhao, Qiuni; Jiang, Yadong; Tai, Huiling (Nano energy, 2023)
Humidity sensor has important applications in environmental and physiological monitoring. With the emergence of self-powered sensor systems, developing self-powered wireless humidity sensor system is highly attractive, but how to realize the humidity sensor with high humidity sensing and power generation performances to achieve self-powered humidity detection system is full of challenges. Herein, we proposed a self-powered electrochemical humidity (ECH) sensor with primary battery structure, using NaCl and hydroxylated multi-walled carbon nanotubes (OH-MWCNTs) as humidity sensing electrolyte, and MnO2 and Al as electrodes. The hygroscopic and ionic conductivity characteristics of the NaCl/OH-MWCNTs electrolyte endow the ECH sensor with spontaneous voltage generation in a wide humidity range of 10.9–91.5 % relative humidity (RH) at room temperature of 25 °C. Notably, a single ECH sensor can output 1.32 V with a maximal power of 20.52 μW at 91.5 % RH. Furthermore, the ECH sensor can be used for respiratory rate monitoring, non-contact switch and visual humidity indication. As a proof of concept, we successfully designed a prototype of self-powered wireless humidity monitoring system based on ECH sensor. This work not only provides a new strategy for developing high-performance ECH sensor, but also provides a reference for the self-powered wireless humidity monitoring system of the ECH sensor. [Display omitted] •The proposed electrochemical humidity (ECH) sensor can spontaneously output voltage in a wide humidity range of 10.9–91.5 % RH.•The ECH sensor can output 1.32 V with a maximal power of 20.52 μW at 91.5 % RH.•The ECH sensor has potential applications in respiratory rate monitoring, non-contact switch and visual humidity indication.•A prototype of self-powered wireless humidity monitoring system based on ECH sensor is successfully designed.